1996
DOI: 10.1097/00005373-199608000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cytokines and Prostaglandin E sub 2 by Subpopulations of Guinea Pig Enterocytes

Abstract: These observations may be important because, as gut integrity is compromised after thermal injury, enterocytes that may have previously been unexposed or less exposed to endotoxin can become a significant source of inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The finding that IL-6 was not increased in 17␤-estradiol-pretreated males 2 h after hypoxemia further suggests that 17␤-estradiol prevented the increased release of this cytokine by Kupffer cells. Nonetheless, studies also support other tissues (i.e., gut) as an important source of IL-6 after injury (8,23). In this regard, Nelson et al (21) showed that inhibition of gut-derived IL-6 with pentoxifylline improved survival after sepsis.…”
Section: Discussionmentioning
confidence: 92%
“…The finding that IL-6 was not increased in 17␤-estradiol-pretreated males 2 h after hypoxemia further suggests that 17␤-estradiol prevented the increased release of this cytokine by Kupffer cells. Nonetheless, studies also support other tissues (i.e., gut) as an important source of IL-6 after injury (8,23). In this regard, Nelson et al (21) showed that inhibition of gut-derived IL-6 with pentoxifylline improved survival after sepsis.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, it is not surprising that Meakins and Marshall have suggested that the gastrointestinal track may be the "motor" for producing multiple organ failure following injury [26]. It has also been shown that intestinal epithelial cells produce interleukin-6 (IL-6) [27] and tumor necrosis factor (TNF) [28]. Despite the fact that enterocytes are capable of producing inflammatory cytokines following in vitro endotoxin stimulation [27,28], our recent studies have indicated that organs other than the gut appear to be responsible for upregulating proinflammatory cytokines during polymicrobial sepsis [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that intestinal epithelial cells produce interleukin-6 (IL-6) [27] and tumor necrosis factor (TNF) [28]. Despite the fact that enterocytes are capable of producing inflammatory cytokines following in vitro endotoxin stimulation [27,28], our recent studies have indicated that organs other than the gut appear to be responsible for upregulating proinflammatory cytokines during polymicrobial sepsis [29]. It is postulated that mediators such as norepinephrine released by the gut [30] stimulate the tissue fixed macrophages in the liver (i.e., Kupffer cells) to produce the proinflammatory cytokine TNF via ␣-adrenergic receptors [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these concentrations are inheren tly difficult to estimate, because they may be influenced by cytokine concentrations circulating systemi cally as well as cytokines produced locally by enterocytes and intraepithelial lymphocytes. [56][57][58] Use of a physiologically relevant model of disease, in conjunction with evaluation using key mediators of inflammation in vitro, gives credence to our results.…”
Section: Discussionmentioning
confidence: 55%